Android-Based Educational Game Learning Media Containing Gending Rare Local Wisdom on Science Subjects for Grade 5 Elementary Schools - Ni Made Milayani Suarningsih; I Gede Margunayasa; I Wayan Lasmawan (Universitas Pendidikan Ganesha, 2024)
Android-based educational game media based on local wisdom, Gending Rare, is a solution to the problem of low student learning outcomes. This research aims to produce Android-based educational game learning media containing local wisdom of gending rare in science subjects for grade 5 elementary school. This research is development research using the ADDIE model. This model is divided into five steps, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The research results are; (1) Android-Based Educational Game Learning Media Containing Gending Rare Local Wisdom in Science Subjects for Grade 5 Elementary School in the form of an application that can be installed on a smartphone. (2) The validity test obtained the qualification